Drugs, parents, and children the three-way connection - Rosenthal, Mitchell S.; Mothner, Ira (Houghton Mifflin, 1972)
"Here is a book that refuses to coddle the illusions of either side of the generation gap about drugs and their dangers. It is a book written from intimate experience and clear knowledge. Above all, it is a book that can really help".--Cover.